Neuromechanisms of SARS-CoV-2: A Review - DosSantos, Marcos F.; Devalle, Sylvie; Aran, Veronica; Capra, Daniela; Roque, Natália Roberta; Coelho-Aguiar, Juliana de Mattos; Spohr, Tânia Cristina Leite de Sampaio e; Subilhaga, Janice Gonçalves; Pereira, Cláudia Maria; D'Andrea Meira, Isabella; Niemeyer Soares Filho, Paulo; Moura-Neto, Vivaldo (Frontiers in Neuroanatomy, 2020)
Recent studies have suggested the neuroinvasive potential of severe acute respiratory coronavirus 2 (SARS-CoV-2). Notably, neuroinvasiveness might be involved in the pathophysiology of coronavirus disease 2019 (COVID-19). Some studies have demonstrated that synapse-connected routes may enable coronaviruses to access the central nervous system (CNS). However, evidence related to the presence of SARS-CoV-2 in the CNS, its direct impact on the CNS, and the contribution to symptoms suffered, remain sparse. Here, we review the current literature that indicates that SARS-CoV-2 can invade the nervous system. We also describe the neural circuits that are potentially affected by the virus and their possible role in the progress of COVID-19. In addition, we propose several strategies to understand, diagnose, and treat the neurological symptoms of COVID-19.